ChemInform Abstract: Synthesis of 7‐Triazole‐Substituted Camptothecin via Click Chemistry and Evaluation of in vitro Antitumor Activity. Issue 29 (22nd July 2014) - Wang, Lei; Yuan, Wei; Zhang, Jie; Tong, Linjiang; Luo, Yu; Chen, Yi; Lu, Wei; Huang, Qingqing
Abstract To discover more potent antitumor agents, title compounds (III) are synthesized via Huisgen cycloaddition reaction of 7‐alkyne‐substituted camptothecin (I).